1996
DOI: 10.1524/ract.1996.75.4.179
|View full text |Cite
|
Sign up to set email alerts
|

Complexation and Transport of Uranyl Nitrate in Supercritical Carbon Dioxide with Organophosphorus Reagents

Abstract: Experiments have been performed to evaluate the feasibility of extracting solid uranyl nitrate with organophosphorus ligands using supercritical carbon dioxide as a solvent. Ligands investigated include tri-n-butylphophate (TBP), tributyl phosphine oxide (TBPO), trioctyl phosphine oxide (TOPO) and triphenyl phosphine oxide (TPPO). Of these ligands, TBP demonstrated the most favorable ligand behavior, forming stable complexes with uranyl nitrate, and showing excellent transport capabilities. TOPO and TBPO showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 11 publications
0
36
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Among these studies, a method has been studied in which decladded spent fuels are "directly" treated by the supercritical fluid, a single-phase mixture of HNO3, H2O and tri-n-butylphosphate (TBP) in supercritical carbon dioxide (SC-CO2). [9][10][11] Here, "directly" means "without a dissolution process".…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Among these studies, a method has been studied in which decladded spent fuels are "directly" treated by the supercritical fluid, a single-phase mixture of HNO3, H2O and tri-n-butylphosphate (TBP) in supercritical carbon dioxide (SC-CO2). [9][10][11] Here, "directly" means "without a dissolution process".…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] It is particularly worth noting that an alternative and more attractive method of supercritical CO2 technology is "direct leaching" of metals from solid samples by utilizing a large penetration force and high diffusivity of supercritical CO2 into the solids. [9][10][11][12][13][14][15][16][17][18] In order to extract uranium from radioactive wastes, the authors have developed a novel extraction method, 12 in which supercritical CO2 containing a reactant is used as a medium to dissolve metal compounds involved in a solid matrix. It was demonstrated that the method using a nitric acid-tri-n-butyl phosphate (HNO3-TBP) complex as an extractant was applicable to the extraction of uranium from simulated radioactive waste samples contaminated by uranium oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Supercritical fluid extraction (SFE) using an extractant-supercritical CO 2 mixture instead of an extractant-organic solvent mixture has recently been recognised to be promising as an advanced method for separation of metals from liquid samples or even from solid samples for the purpose of analytical pretreatment or hydrometallurgy. Hence, an increasing number of studies on the development of SFE of metals (Laintz and Tachikawa, 1994;Furton et al, 1995;Iso et al, 1995;Lin et al, 1995;Meguro et al, 1996;Toews et al, 1996;Wang and Wai, 1996;Smart et al, 1997) are available. One of several important advantages of SFE is that extraction efficiency and extraction selectivity can be enhanced by tuning the pressure and/or temperature.…”
mentioning
confidence: 99%